Pengaruh Ukuran Perusahaan, Leverage dan Profitabilitas terhadap Harga Saham: (Studi Pada Perusahaan Properti dan Real Estate yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2023) - Amin Hou; Ahmad Rivai; Indah Juwita (Jurnal Manajemen dan Ekonomi Kreatif, 2024)
The aim of this research is to partially test and analyze the influence of each variable Company Size, Leverage and Profitability on stock prices (2) To test and analyze the influence of Company Size, Leverage and Profitability simultaneously on Stock Prices. This type of research is causal quantitative research, the data source used is secondary data. The data analysis technique uses multiple linear regression. Data collection methods consist of library studies and documentation. As well as the sampling technique using the Purposive Sampling method with research data from 30 Property and Real Estate companies listed on the IDX as the population and 18 companies as the sample. The t test results show that partially, Company Size (L.N.T.ASSETS) has a negative and significant effect, Leverage (DER) has a positive and significant effect, Profitability (ROA) has a negative and insignificant effect on share prices listed on the Indonesia Stock Exchange. The results of the f test show that Company Size (L.N.T.ASSETS), Leverage (DER), Profitability (ROA) simultaneously have a significant effect on Share Prices (PER) listed on the Stock Exchange in Indonesia.